1998
DOI: 10.1086/515301
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐12‐Dependent Mechanisms in the Clearance of Blood‐Stage Murine Malaria ParasitePlasmodium bergheiXAT, an Attenuated Variant ofP. bergheiNK65

Abstract: The mechanism of development of host resistance to blood-stage malarial infection was studied by use of an irradiation-induced attenuated variant, Plasmodium berghei XAT, obtained from a lethal strain, P. berghei NK65. The infection enhanced mRNA expression of interleukin (IL)-12 p40 and also of interferon (IFN)-gamma, IL-4, IL-10, and cytokine-inducible nitric oxide synthase (iNOS) in spleen. Treatment of these mice with anti-IL-12 or anti-IFN-gamma led to the progression of parasitemia and fatal outcome. Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 32 publications
(4 reference statements)
2
28
0
Order By: Relevance
“…This IL-12-induced protection is mediated by IFN-␥ and TNF-␣ (15) and requires the presence of NK and CD4 ϩ T cells (15,16). A similar protective effect of IL-12 treatment was also shown in mice infected with a radiation-attenuated variant of Plasmodium berghei (17) or liver-stage Plasmodium yoelli (18). We have also shown that resistant C57BL/6 mice mount a strong IL-12 response within 2-3 days of P. chabaudi AS infection while this response is impaired in susceptible A/J mice.…”
Section: Il-12 Is Required For Antibody-mediated Protective Immunitysupporting
confidence: 78%
See 1 more Smart Citation
“…This IL-12-induced protection is mediated by IFN-␥ and TNF-␣ (15) and requires the presence of NK and CD4 ϩ T cells (15,16). A similar protective effect of IL-12 treatment was also shown in mice infected with a radiation-attenuated variant of Plasmodium berghei (17) or liver-stage Plasmodium yoelli (18). We have also shown that resistant C57BL/6 mice mount a strong IL-12 response within 2-3 days of P. chabaudi AS infection while this response is impaired in susceptible A/J mice.…”
Section: Il-12 Is Required For Antibody-mediated Protective Immunitysupporting
confidence: 78%
“…For murine malaria, a protective effect of IL-12 has also been shown in P. berghei XAT infection in CBA mice (17). Furthermore, studies in P. yoelii-infected BALB/c (30) and P. berghei XAT-infected CBA mice (31) also demonstrate that Th1-associated IgG2a and IgG3 are the major protective Ab subclasses in Ab-mediated immunity against blood-stage malaria.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, high levels of IL-10 expression were found to protect mice against CM by suppressing proinflammatory cytokines (42,43). Recently, it was shown that IL-12 production was necessary for the development of protective immunity against blood-stage infection with an attenuated P. berghei strain, and that this effect was dependent on IFN-␥ production by CD4 ϩ T cells (44). However, IL-12 production was also shown to induce immune pathology rather than protection using a more virulent P. berghei strain.…”
Section: Discussionmentioning
confidence: 99%
“…IL-12, composed of two heterologous chains (p35 and p40), is known to confer protection against disease as well as causing host pathogenicity during infection with malaria parasites, which can be explained through the activation of IFN-γ-producing Th1 CD4 + T cells [16][17][18]. These findings were observed in p40-lacking mice deficient in not only IL-12, but also IL-23 (the p40 subunit is shared between IL-12 and IL-23), raising a possibility that the phenomena attributed to IL-12 might in fact be due to IL-23.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this cytokine restricts the growth of intracellular pathogens in an IL-17-dependent manner [13][14][15]. However, there are only a few reports about whether or not IL-23 plays a protective role against malaria parasites residing in red blood cells (RBCs). IL-12, composed of two heterologous chains (p35 and p40), is known to confer protection against disease as well as causing host pathogenicity during infection with malaria parasites, which can be explained through the activation of IFN-γ-producing Th1 CD4 + T cells [16][17][18]. These findings were observed in p40-lacking mice deficient in not only IL-12, but also IL-23 (the p40 subunit is shared between IL-12 and IL-23), raising a possibility that the phenomena attributed to IL-12 might in fact be due to IL-23.…”
mentioning
confidence: 99%